Implementasi Model Desa Wisata Edukatif Sebagai Media Pembelajaran Mahasiswa Berbasis Merdeka Belajar Kampus Merdeka (MBKM) di Desa Wisata Cisaat, Kabupaten Subang, Jawa Barat - Revi Agustin Aisyianita; Darmawan Rahmat; Jenal Abidin; Lala Siti Sahara; Rezka Fedrina; Erdawati (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2022)
The purpose of this activity is to prepare Pokdarwis in managing educational tourism (which includes: tour packages, interpretation media, and supporting tools such as modules and Student Worksheets). In addition, this program is expected to be able to provide debriefing and learning space for students who are interested in learning about destination management and creating educational tour packages. The results of this program include (1) Cisaat educational tour package; (2) 12 educational tourism interpretation media; (3) the module books and worksheets as supporting tools for educational tourism. At the end of the program, the evaluation results showed a positive response from all participants, both from the community, junior high school students, and UNJ students.